Informed Consent, Biobank Research, and Locality: Perceptions of Breast Cancer Patients in Three European Countries. (July 2014) - Petersen, Imme; Desmedt, Christine; Harris, Adrian; Buffa, Francesca; Kollek, Regine
Comparative studies are missing that explore how socio-cultural and institutional circumstances influence patient comprehension and expectations regarding informed consent for current and future research on their tissue and data. This study compares how breast cancer patients in three European countries (the United Kingdom, Belgium, and Germany) who have consented to participate in tumor banking assess the given consent and the accompanying local contextual factors influencing it. Our survey demonstrates that only 59% of the patients in the British survey, but about 90% in the German and Belgian surveys, correctly recalled tissue and data donation for study purposes. Of those who remembered the study participation status correctly, about 90% had altruistic motives. At the same time, approximately half of the survey participants, or even 70% of the Belgians, expected personal benefit from research participation and information on cancer risk within the family. About half of the interviewees, but only 27% of the British participants, definitively wanted to be asked for re-consent for future research. Of the local contextual factors under study, participants' appraisals of medical science and data protection were particularly pertinent. More culturally and contextually sensitive comparative research is needed to better understand patient attitudes toward research participation and tissue donation in the context of biobank research.